Integrated natural resources management - Wang, Lawrence K.; Wang, Mu-Hao Sung; Hung, Yung-Tse; Shammas, Nazih K. (Springer, 2021)
This edited book has been designed to serve as a natural resources engineering reference book as well as a supplemental textbook. This volume is part of the Handbook of Environmental Engineering series, an incredible collection of methodologies that study the effects of resources and wastes in their three basic forms: gas, solid, and liquid. It complements two other books in the series including "Natural Resources and Control Processes" and "Environmental and Natural Resources Engineering". Together they serve as a basis for advanced study or specialized investigation of the theory and analysis of various natural resources systems. The purpose of this book is to thoroughly prepare the reader for understanding the topics of global warming, climate change, glacier melting, salmon protection, village-driven latrines, engineers without borders (USA), surface water quality analysis, electrical and electronic wastes treatment, water quality control, tidal rivers and estuaries, geographic information systems, remote sensing applications, water losses investigations, wet infrastructure, lake restoration, acidic water control, biohydrogen production, mixed culture dark anaerobic fermentation, industrial waste recycle, agricultural waste recycle, recycled adsorbents, heavy metals removal, magnetic technology, recycled biohydrogen materials, lignocellulosic biomass, extremely halotolerant bacterial communities, salt pan and salt damaged soil. The chapters provide information on some of the most innovative and ground-breaking advances in resources conversation, protection, recycling, and reuse from a panel of esteemed experts.